Image processing based automatic diagnosis of glaucoma using wavelet features of segmented optic disc from fundus image - Singh, Anushikha; Dutta, Malay Kishore; ParthaSarathi, M; Uher, Vaclav; Burget, Radim (Computer methods and programs in biomedicine, 2016)
Glaucoma is a disease of the retina which is one of the most common causes of permanent blindness worldwide. This paper presents an automatic image processing based method for glaucoma diagnosis from the digital fundus image. In this paper wavelet feature extraction has been followed by optimized genetic feature selection combined with several learning algorithms and various parameter settings. Unlike the existing research works where the features are considered from the complete fundus or a sub image of the fundus, this work is based on feature extraction from the segmented and blood vessel removed optic disc to improve the accuracy of identification. The experimental results presented in this paper indicate that the wavelet features of the segmented optic disc image are clinically more significant in comparison to features of the whole or sub fundus image in the detection of glaucoma from fundus image. Accuracy of glaucoma identification achieved in this work is 94.7% and a comparison with existing methods of glaucoma detection from fundus image indicates that the proposed approach has improved accuracy of classification.
Keywords: dospělí; Wavelet Analysis; interpretace obrazu počítačem; subtrakční technika; Female; vlnková analýza; discus nervi optici; Glaucoma; Adult; Image Interpretation, Computer-Assisted; Subtraction Technique; ženské pohlaví; mladý dospělý; Adolescent; Reproducibility of Results; strojové učení; retinoskopie; lidé; Sensitivity and Specificity; vylepšení obrazu; senzitivita a specificita; Algorithms; Pattern Recognition, Automated; Image Enhancement; rozpoznávání automatizované; reprodukovatelnost výsledků; Male; glaukom; Aged; Machine Learning; Young Adult; Retinoscopy; algoritmy; lidé středního věku; senioři; mužské pohlaví; Middle Aged; mladiství; Optic Disk; Humans